Terrorism and international justice - Sterba, James P. (Oxford University Press, 2003)
pt. I. What is the nature and rhetoric of terrorism? Murderers, not warriors: the moral distinction between terrorists and legitimate fighters in asymmetric conflicts / Shannon E. French ; The terrorism of "terrorism" / Tomis Kapitan -- pt. II. Who are the terrorists, and why do they hate? Terror and just response / Noam Chomsky ; Narratives competing for our souls / David B. Burrell ; The war against pluralism / Robert L. Phillips ; Can a Muslim be a terrorist? / Zayn Kassam -- pt. III. What is a morally justified response to terrorism? The moral response to terrorism and cosmopolitanism / Louis P. Pojman ; Envisioning a global rule of law / Daniele Archibugi and Iris Marion Young ; Making war on terrorism in response to 9/11 / Claudia Card ; Terrorism, war, and empire / Richard W. Miller ; Terrorism and international justice / James P. Sterba ; Compassion and terror / Martha C. Nussbaum